What is the correlation between the defective and splitting posterior segmental bronchus and recurrent artery crossing intersegmental planes in the right upper lobe? - Li, Zhikai; Kong, Yuhong; Wu, Wenbo; Chen, Shuangqing; Zhang, Xiaopeng (Frontiers in Surgery, 2023)
Abstract Background: With the prevalence of three-dimensional computed tomography bronchography and angiography (3D-CTBA) and the development of anatomical segmentectomy, studies have confirmed the increased incidence of anomalous veins in patients with tracheobronchial abnormalities. Nevertheless, the characteristic anatomical correlation between bronchus and artery variation remains unknown. Thus, we conducted a retrospective study to investigate recurrent artery crossing intersegmental planes and their associated pulmonary anatomical features by analyzing the incidence and types of the right upper lobe (RUL) bronchus and the artery composition of the posterior segment. Materials and Methods: A total of 600 patients with ground-glass opacity who had undergone 3D-CTBA preoperatively at Hebei General Hospital between September 2020 and September 2022 were included. We reviewed the anatomical variations of the RUL bronchus and artery in these patients using 3D-CTBA images. Results: Among all 600 cases, the defective and splitting B2 contained four types of the RUL bronchial structure: B1 + BX2a, B2b, B3 (11/600, 1.8%); B1, B2a, BX2b + B3 (3/600, 0.5%); B1 + BX2a, B3 + BX2b (18/600, 3%); B1, B2a, B2b, B3 type (29/600, 4.8%). The incidence of recurrent artery crossing intersegmental planes was 12.7% (70/600). The incidence of recurrent artery crossing intersegmental planes with and without the defective and splitting B2 was 26.2% (16/61) and 10.0% (54/539), respectively (p < 0.005). Conclusions: In patients with defective and splitting B2, the incidence of recurrent artery crossing intersegmental planes was increased. Our study provides certain references that surgeons can use to plan and perform RUL segmentectomy.